PERANCANGAN DAN IMPLEMENTASI HUMAN RESOURCE INFORMATION SYSTEM PADA TOKO RUMAH NENEK BERBASIS WEB - Siddharta Prajna Putra; Joko Susilo (Institut Bisnis dan Informatika Kwik Kian Gie, 2021)
“Toko Rumah Nenek” is a micro, small and medium enterprise (MSME) whose main activity is selling various kinds of fruit. A supporting internal system is required to support the competent human resources. “Toko Rumah Nenek” still uses the manual system for the attendance recaps, leave permits, overtime permits, letter requests for personal needs, and salary slips. HRD (Human Resource Department) and the owner also have difficulties in finding the personal data of employees to fulfill all the requested needs.To support the thesis writing, researchers use theories related to the design to be made such as information, information systems, data, payroll, HR, HRIS, Java, user interface, Spring Boot, My SQL, Java Script, HTML, CSS, use case and ERD. Several previous studies were also used to assist the research process carried out. This research uses the Waterfall method that each stage- structured could minimize errors with a clear direction. Information was collected using field studies, namely observation and interviews. All information obtained will be processed for website information design because it is directly from the source.Java programming language is used in this research with the Framework Spring Boot. The result is that the user could manage the recaps of employee’s attendance, document request, leave permits, and employee payroll with the integrated web-based HRIS. It is concluded that HRIS could facilitate the easier and faster process of human resources by HRD or the owner due to the integrated HRIS. This system could be accessed by the user through the website. This research is expected to be developed by the next researcher. Keywords: Human Resource, Human Resource Information System (HRIS), website, Java, Springboot.